ANALISIS NORMATIF UNDANG-UNDANG NOMOR 14 TAHUN 2005 SEBAGAI IMPLEMENTASI PERLINDUNGAN TENAGA PENDIDIK (Studi Kasus Penganiayaan Guru SMAN 1 Torjun Sampang Jawa Timur) - Muhlis Fahdiar Sembiring (STKIP Budidaya Binjai, 2018)
Educators are an important role in the formation of human resources as a nation's strength in fortifying themselves in cognitive, affective, and psychomotor concepts. The success of a nation does not escape the role of educators in the equitable development of knowledge and technology. Competitiveness is so high as the development of globalization requires human resources to always be able to develop both in terms of hard skills and soft skills. Based on this, educators are expected to have competence in the application of the learning and teaching process. Legal events that occur in this study are not only the responsibility of educational institutions, but the factors of the family are very influential on the pattern of child development, because the family is the first place and place where children spend more time in the family environment. The way students are applied by parents is also very influential on children's attitudes. Parenting that tends to spoil also shapes the attitude of children who are accustomed to what they want to be fulfilled and with such a pattern of life the child does not learn to control emotions and not learn to manage themselves Law enforcement is a process that is essentially the implementation of directors which involves making decisions that are not strictly regulated by the rule of law but have elements of personal judgment. Conceptually, the core and meaning of law enforcement lies in harmonizing the relationships of values described in solid rules and attitude to act as a series of final stages of value translation, to create, give birth and maintain the peace of life.